Trickle-Down Engagement: Maximizing Teacher and Student Engagement in First-Year Courses - Saucier, Donald; Miller, Stuart (My University, 2017)
While much research has examined the engagement of college students in the classroom, relatively little research has examined the engagement of their teachers. This session explores the possibility that enhancing the engagement of college teachers will “trickle down” to enhance the engagement (and learning) of their students. Presenters will explore the results of their research program investigating college teachers’ subjective experiences in teaching, the correlates of these experiences, and the outcomes these experiences have on students’ engagement and learning. The data supports the “trickle-down engagement” model, and suggests practical recommendations to improve the engagement of both college faculty and students in their shared courses.
Citation: Saucier, D., & Miller, S. (2017). Trickle-Down Engagement: Maximizing Teacher and Student Engagement in First-Year Courses. 36th Annual Conference on the First-Year Experience, Atlanta, GA.
Keywords: Trickle-down engagement; First-year experience program; Engagement; Student Learning K-State Book Network (KSBN); Faculty development